1968
DOI: 10.1177/002199836800200107
|View full text |Cite
|
Sign up to set email alerts
|

Some Fundamental Fracture Mechanisms Applicable to Advanced Filament Reinforced Composites

Abstract: The object of this study is to establish experimentally the critical fracture modes of an epoxy m a t r i x in the vicinity of a break in a high modulus, high strength filament. Three distinct failure modes were observed to occur and the nature of these three modes is explained through an analysis of the s t r e s s state in the matrix. A single filament embedded in an epoxy novolac was used to examine the fracture process.this type of resin a r i s e s f r o m its ability to be modified to varying degrees of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(31 citation statements)
references
References 3 publications
1
30
0
Order By: Relevance
“…Three failure modes are encountered; a transverse matrix crack, an inclined conical matrix crack and/or fibre/matrix debond [3,4]. The failure mode depends on the quality of interface [4] as indicated below; (a) If the interface is strong in an elastic matrix, a fibre-break is accompanied by a transverse matrix crack.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Three failure modes are encountered; a transverse matrix crack, an inclined conical matrix crack and/or fibre/matrix debond [3,4]. The failure mode depends on the quality of interface [4] as indicated below; (a) If the interface is strong in an elastic matrix, a fibre-break is accompanied by a transverse matrix crack.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by various authors [3,4,6,7 ] have shown that matrix cracks propagate with applied strain, perpendicular to the fibre fracture. Matrix cracks which form at lower applied strains propagate a shorter distance into the polymer than those which form at high strains, because of a lower stored elastic energy [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in a same composite material, wave attenuation is more significant in cracked than in healthy state, which will complicate the signal processing after few damage modes have developed, especially for the amplitude distribution. Qualifying damage started first in 2D composites and Mehan and Mullin in 1968 [2] managed to identify three basic failure mechanisms: (i) fiber fracture; (ii) matrix cracking; (iii) and fibre/matrix interfacial debonding. The authors reported the application of AE in composites in 1971 [3], discriminating audible types for these three basic damage modes using an AE system.…”
Section: Damage Monitored By Acoustic Emissionmentioning
confidence: 99%